Comparison of Total Extra Peritoneal and Transabdominal Pre-Peritoneal Inguinal Hernia Repair - Raza, Ali; Fayyaz, Muhammad Usman; Malik, Maria Naseer (Indus Journal of Bioscience Research, 2025)
Objectives: To compare the laparoscopic TEP technique with the TAP for inguinal hernia repair. Study Design: Randomized controlled trial (RCT). Place and Duration of Study: Department of General Surgery, Holy Family Hospital, Rawalpindi from 30th November 2023 to 29th May 2024. Methodology: A total of 150 patients with inguinal hernia were included. Patients were allocated to the two groups (Group A: Total Extra Peritoneal and Group B: Transabdominal Pre-Peritoneal). Results: In our study, mean operative time in TEP group was 64.31 ± 7.35 minutes while in TAPP group was 87.20 ± 6.01 minutes. Mean post-operative pain in TEP was 1.87 ± 1.08 while in TAPP group was 4.11 ± 1.44. Mean hospital stay in TEP was 1.73 ± 0.66 days while in TAPP was 5.15 ± 0.90 days. Mean time to return to daily work in TEP group was 5.45 ± 1.22 days while in TAPP was 10.28 ± 2.89 days. Conclusion: This study concluded that mean operative time, mean postoperative pain, mean hospital stay and time to return to daily work is less after TEP technique for inguinal hernia repair as compared to laparoscopic TAPP repair